Atomic force microscopy investigation of the interaction of low-level laser irradiation of collagen thin films in correlation with fibroblast response. Issue 9 (December 2015) - Stylianou, Andreas; Yova, Dido
Abstract Low-level red laser (LLRL)–tissue interactions have a wide range of medical applications and are garnering increased attention. Although the positive effects of low-level laser therapy (LLLT) have frequently been reported and enhanced collagen accumulation has been identified as one of the most important mechanisms involved, little is known about LLRL–collagen interactions. In this study, we aimed to investigate the influence of LLRL irradiation on collagen, in correlation with fibroblast response. Atomic force microscopy (AFM) and fluorescence spectroscopy were used to characterize surfaces and identify conformational changes in collagen before and after LLRL irradiation. Irradiated and non-irradiated collagen thin films were used as culturing substrates to investigate fibroblast response with fluorescence microscopy. The results demonstrated that LLRL induced small alterations in fluorescence emission and had a negligible effect on the topography of collagen thin films. However, fibroblasts cultured on LLRL-irradiated collagen thin films responded to LRLL. The results of this study show for the first time the effect of LLRL irradiation on pure collagen. Although irradiation did not affect the nanotopography of collagen, it influenced cell behavior. The role of collagen appears to be crucial in the LLLT mechanism, and our results demonstrated that LLRL directly affects collagen and indirectly affects cell behavior.